Bairro verde - Godoy, Veridiana Emília [UNESP]; Carneiro, Felipe Alves [UNESP]; Fontes, Maria Solange Gurgel de Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The University Extension project "Green Neighborhood" has the specific focus on urban trees, chosen by the benefits that spread throughout urban environment , whether environmental, economic, social and, thus, to contribute to the improvement of people's quality of life. The project aims to encourage urban trees and improving the configuration of living spaces in neighborhoods of the city of Bauru. The Jardim Panorama was the "pilot" in 2014 and in 2015 is the Jardim Marambá.

O projeto de Extensão Universitária “Bairro Verde” tem como foco específico a arborização viária, escolhida pelos benefícios que dissemina por todo ambiente urbano, seja ambiental, econômica, social e, assim, poder contribuir para a melhoria da qualidade de vida da população. O projeto visa incentivar a arborização viária e a melhoria da configuração dos espaços de convívio em bairros da cidade de Bauru. O Bairro Jardim Panorama foi o "piloto", em 2014, e em 2015, o Jardim Marambá.
Keywords: Urban trees; Environmental quality; Arboreal planning; Arborização viária; Qualidade ambiental; Planejamento arbóreo